The Effect of Seaweed Extract (Sargassum Sp) Used as Fertilizer on Plant Growth of Capsicum Annum (Chilli) and Lycopersicon Esculentum (Tomato) (Indonesian Journal of Science and Technology, 2024)
Seaweeds, mainly brown species, have long been used as soil fertilizers and have several advantageous effects of spraying their crude extracts on plant growth. Unlike chemical fertilizer, biofertilizers derived from seaweeds or other organisms are usually biodegradable, non-toxic, non-polluting and non-hazardous to humans, animals and birds which will benefit to agriculture sector. In this study, four different concentrations (0.50; 1.00; 2.50; and 5.00 mg/L) of four different solvents extract (hexane, dichloromethane, methanol and water) were used to determine the effect on in vitro seed germination of Capsicum annum and Lycopersicon esculentum. The results showed that concentration 2.50 mg/L can be classified as optimum concentration for seedling development of Lycopersicon esculentum and this study has proven that DCM is the effective extract solvent that result in promoting hypocotyl and root growth of tomato plant. For Capsicum annum, hexane extracts solvent of Sargassum sp. Was found to be more effective than other extracts in promoting seedlings development. Phytochemical screening of Sargassum sp. exhibited the presence of alkaloids and terpenoids as the dominant compenants in all extract.